2013
DOI: 10.1302/2046-3758.22.2000066
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibition of 5-lipoxygenase enhances bone formation in a rat model

Abstract: ObjectivesRecent studies have shown that modulating inflammation-related lipid signalling after a bone fracture can accelerate healing in animal models. Specifically, decreasing 5-lipoxygenase (5-LO) activity during fracture healing increases cyclooxygenase-2 (COX-2) expression in the fracture callus, accelerates chondrogenesis and decreases healing time. In this study, we test the hypothesis that 5-LO inhibition will increase direct osteogenesis.MethodsBilateral, unicortical femoral defects were used in rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Fracture healing in long-term COX2 deficiency was demonstrated to be impaired [47]. In contrast, reduction of 5-LOX is associated with enhanced fracture healing, including elevated callus chondrogenesis and osteogenesis [11, 48, 49]. Somjen et al showed that baicalein blocks parathormone (PTH)-induced DNA synthesis unless 12- and 15-lipoxygenase are added [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fracture healing in long-term COX2 deficiency was demonstrated to be impaired [47]. In contrast, reduction of 5-LOX is associated with enhanced fracture healing, including elevated callus chondrogenesis and osteogenesis [11, 48, 49]. Somjen et al showed that baicalein blocks parathormone (PTH)-induced DNA synthesis unless 12- and 15-lipoxygenase are added [50].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of bone resorption markers such as Trap and Rankl as well as Il-7 may explain the phenomenon of reduced early callus formation. However, the finding that 5-lipoxygenase knockout mice developed a callus rapidly and the bone healed faster [11, 48] contradicts this theory and could indicate that the inhibition of 5-LOX is not the only pathway through which baicalein manipulates bone healing. The inhibition of NF-κB by baicalein can have serious adverse effects through the whole bone-healing process [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 5‐LO has been considered a key mediator of RANKL‐induced osteoclast formation (Lee et al., ; Moura et al., ). Other studies have also shown that the inhibition of 5‐LO is associated with increased bone formation (Cottrell, Keshav, Mitchell, & O'Connor, ; Gallwitz et al., ; Manigrasso & O'Connor, ). Therefore, the results presented herein show that the absence of 5‐LO decreased recruitment and differentiation of osteoclast precursors after Aa infection and consequently impaired alveolar bone loss.…”
Section: Discussionmentioning
confidence: 91%
“…Lipoxygenase (LOX) inhibitors have been found to suppress osteoclast formation and enhance bone formation in vivo ( 8 , 9 ). A LOX inhibitor, Baicalein, which is extracted from the plant Scutellaria baicalensis inhibits 12- and 15-Lipoxygenase ( 12 - and 15-LOX ).…”
Section: Introductionmentioning
confidence: 99%